2019
DOI: 10.1139/cgj-2017-0732
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness– and damping–strain curves of sensitive Champlain clays through experimental and analytical approaches

Abstract: Stiffness degradation, G/G0, curves of Champlain clay at St-Adelphe, Quebec, and the associated variation of its damping ratio with shear strain are constructed in this study using the new combined triaxial simple shear (TxSS) apparatus. The apparatus offers the ability to obtain the stiffness (G/G0) and damping ratio of soils over a wide strain spectrum from 0.001% to 10%. The value of the small-strain stiffness of the tested clay is further confirmed through another series of piezoelectric ring-actuator tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Murro clay is highly strain anisotropic and time dependent [16]. Many other studies have been investigated for clays [17][18][19]. A large number of C c − w n (C c is the compression index, and w n is the natural water content) correlations have been proposed by researchers for different soft clays around the world, but comparisons of these correlations and reasons for differences between them are rarely reported.…”
Section: Literature Review On Compressible Soilsmentioning
confidence: 99%
“…Murro clay is highly strain anisotropic and time dependent [16]. Many other studies have been investigated for clays [17][18][19]. A large number of C c − w n (C c is the compression index, and w n is the natural water content) correlations have been proposed by researchers for different soft clays around the world, but comparisons of these correlations and reasons for differences between them are rarely reported.…”
Section: Literature Review On Compressible Soilsmentioning
confidence: 99%
“…The area of hysteresis loop is indirectly proportional to the degree of saturation [94] which means high saturation leads to low area under hysteresis loop and low area of loop results in high damping ratio. This can be explained using the equation of damping ratio (D = (1/π)*{A L /(A Δ1 + A Δ2 + A 3 )}, where A L = Area of 4 Hanumanta-Rao and Ramana [116]; 5 Kirar and Maheshwari [117]; 6 Chattaraj and Sengupta [17]; 7 Kumar et al [27]; 8 Paul and Dey [94]; 9 Dammala et al [118]; 10 Matasovic and Vucetic [119]; 11 Chiaradonna et al [120]; 12 Chehat et al [121]] hysteresis loop, A Δ1 = Area of triangle made after joining positive peak to maximum axial strain, A Δ2 = Area of triangle made after joining negative peak to minimum axial strain and A 3 = Area of rectangle made after joining minimum deviator stress to maximum axial strain), i.e., for higher loop area, the denominator increases significantly in turn reduces the damping ratio. The material damping is greatly influenced by the particle-to-particle friction, rate of strain, and its non-elastic behavior.…”
Section: Influence Of σ C ' Rc F and γ On Damping Ratio Of Silt-rich Fly Ashmentioning
confidence: 99%
“…Javed (2011) found that the effect of loading frequency decreases as the number of loading cycle increases. Recently, Chehat et al (2019) presented a constitutive model for an over consolidated Champlain clay at St-Adelphe, Quebec using a combined triaxial simple shear D r a f t apparatus. The model includes pore-water pressure built up with shear strain.…”
Section: Introductionmentioning
confidence: 99%
“…The model includes pore-water pressure built up with shear strain. The studies discussed so far focused on the large-strain behavior of Leda clays corresponding to a strain level of 0.01-10%, and very few studies have been conducted on the low-strain behavior corresponding to a strain level of less than 0.001% (Chehat et al 2019). Characterizing the low-strain behavior of Leda clays is important for quantifying the dynamic response, particularly during earthquakes.…”
Section: Introductionmentioning
confidence: 99%